The Concept of Corruption Prevention Using a Transcendental Approach - Mukhlishin, Mukhlishin (Journal of Transcendental Law, 2020)
Corruption in Indonesia has injured the nation’s philosophy of being civilized and divine. From the various measures (laws) that have been implemented, the results have not shown the maximum, instead increasing the number of suspects. Prevention of these crimes is urgently needed by exploring the transcendence value of state law based on Pancasila. This study aims to describe the concept of preventing corruption with a transcendental approach. The method used is a literature review and philosophical approach and descriptive analysis. The result is that the concept of preventing the crime of corruption with a transcendental approach must be based on the divinity concept in the first principle of Pancasila by involving religious doctrine as a legal basis that exceeds moral and spiritual boundaries. Belief in the one and only God in Pancasila can create a solid foundation of trust and a self-sacrificing attitude (integrity), conscious servitude to God, and obedience to leaders, and can create values of civility. Pancasila-based legal transcendence is needed in the prevention of corruption. The state is expected to strengthen the divinity doctrine as the basis for the legal trend for citizens.